The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/met9060641
|View full text |Cite
|
Sign up to set email alerts
|

Complex Precipitates of TiN-MCx in GCr15 Bearing Steel

Abstract: Nitride and carbide are the second phases which play an important role in the performance of bearing steel, and their precipitation behavior is complicated. In this study, TiN-MCxprecipitations in GCr15 bearing steels were obtained by non-aqueous electrolysis, and their precipitation mechanisms were studied. TiN is the effective heterogeneous nucleation site for Fe7C3 and Fe3C; therefore, MCxcan precipitate on the surface of TiN easily. The chemistry component of MCx consists of M3C and M7C3 (M = Fe, Cr, Mn) a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…By characterizing the microstructure at different locations in the ingot, it was found that the size of the primary carbides varied with the center segregation in continuous casting [12]. Furthermore, the size of the primary carbides in the central region with a slower cooling rate was the largest, while that in the marginal region was the smallest [16]. The austenite grain could also be refined by adding rare earth elements, thus leading to the further refinement of primary carbides [3,14].…”
Section: Introductionmentioning
confidence: 99%
“…By characterizing the microstructure at different locations in the ingot, it was found that the size of the primary carbides varied with the center segregation in continuous casting [12]. Furthermore, the size of the primary carbides in the central region with a slower cooling rate was the largest, while that in the marginal region was the smallest [16]. The austenite grain could also be refined by adding rare earth elements, thus leading to the further refinement of primary carbides [3,14].…”
Section: Introductionmentioning
confidence: 99%